Repeated-batch fermentation of sugarcane bagasse hemicellulosic hydrolysate to ethanol using two xylose-fermenting yeasts - da Silva, Debora Danielle Virgínio [UNESP]; Machado, Eduardo; Danelussi, Otavio; dos Santos, Miquéias Gomes [UNESP]; da Silva, Silvio Silvério; Dussán, Kelly Johana [UNESP] (Springer Nature, 2022)
In this study, a repeated-batch fermentation of hemicellulosic sugarcane bagasse hydrolysate was investigated to produce bioethanol using two xylose-fermenting yeasts, Scheffersomyces stipitis and Scheffersomyces shehatae. First, diluted-acid pretreatment of sugarcane bagasse at 150 mg H2SO4/g dry bagasse and 127 °C for 10 min, followed by concentration (3.5-fold), and detoxification process led to a hemicellulosic hydrolysate containing 48.97 g L−1 xylose. The hemicellulosic hydrolysate was fermented using repeated-batch operation and studying the performance of S. stipitis and S. shehatae yeasts. The results showed that fermentative parameters through the repeated-batch were significantly increased, and the ability of yeasts was maintained during the two cycles (a total of third rounds). Furthermore, S. shehatae was 85% more efficient in xylose to ethanol conversion than S. stipitis, producing 21.5 g L−1 ethanol that corresponds to YP/S = 0.436 g g−1 and QP = 0.241 g L−1 h−1. In general, the use of sugarcane bagasse hemicellulosic fraction has been proved an excellent alternative to boost bioethanol production together the use of cellulose fraction, to replace fossil fuels. This work showed that the repeated-batch operation and S. shehatae yeast are possible combinations for industrial ethanol production from lignocellulosic hydrolysate.
Keywords: Bioethanol; Hemicellulosic hydrolysate; Repeated-batch; Scheffersomyces shehatae; Scheffersomyces stipitis; Sugarcane bagasse